Structural Models for Lyric-Setting Analysis in Popular Song - Matthew T Hough (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2025)
Studies of English text setting have long focused on "well-formed" examples, typically in 4/4 time, in which syllabic-stress-to-beat matching is prioritized (Halle and Lerdahl 1993, Hayes and Kaun 1996, Hayes 2009). Evidence of this prioritization has been presented in Palmer and Kelly 1992 and Girardi and Plag 2019, and such examples are ubiquitous in English-language nursery rhymes, children’s songs, and folk tunes. The present study contextualizes this type of text setting as one of four models for the structural interaction of English lyrics and music in popular song: 1) unified ("well-formed"), in which musical considerations and a preference for stress matching are molded into agreement; 2) dominated lyric, in which stress matching is of secondary importance to musical concerns; 3) accentuated lyric, in which syllabic stress is emphasized by intentional conflict with a prevailing musical metrical grid; and 4) speech-timed, in which the natural, speechlike rhythm of a lyric–measured in absolute time–structures the example while musical meter and tempo play a subordinate and flexible role. This article includes many close analyses of song recordings. To assist in understanding and following these analyses, the author is hosting a website with streaming audio or video of these recordings. The link to this site is given with each relevant example in the article, and the site as a whole can also be accessed through this link: https://www.matthewhough.com/structuralmodelspaper
Keywords: text setting; lyrics; stress matching; popular song; Kate Bush; Katy Perry; Johnny Ace; The Temptations; Annie Ross; Warren Zevon